PENGEMBANGAN BUKU PENGAYAAN FISIKA TERINTEGRASI ETNOPHYSICS PADA ALAT MUSIK GENDANG MELAYU JAMBI BERBANTUAN HEYZINE FLIPBOOK DAN APLIKASI PHYPHOX - Helmalia Putri Hasibuan, Linda; Jufrida; Shidow Falah, Hebat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop an integrated physics enrichment book on ethnophysics using the traditional Jambi Malay drum (Gendang Melayu Jambi) as a subject. The method used was Research and Development (R&D) with a 4D development model comprising the define, design, development, and disseminate stages. The results showed that in the initial validation stage, the enrichment book received a score of 66.84% from subject matter experts and 69.53% from media experts, both in the “good” category. After revisions were made, the validation results increased to 85.46% and 86.20%, both in the “very good” category. A pilot test involving 36 students showed a positive response to the developed book. Thus, the ethnophysics-based enrichment book on the Gendang Melayu Jambi is suitable for use as supplementary teaching material in physics education.